Factors That Influence Parental Vaccination Decisions for Adolescents, 13 to 17 Years Old: National Immunization Survey–Teen, 2010. (February 2013) - Dorell, Christina; Yankey, David; Kennedy, Allison; Stokley, Shannon
Objectives . We aim to describe factors that influence parental decisions to vaccinate their adolescents. Methods . Data from the July to December 2010 National Immunization Survey–Teen Parental Concerns Module were analyzed to determine factors that influence parental decisions to vaccinate their adolescents. Results . Parents reported that their adolescent's health care provider recommended tetanus toxoid/tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis (Td/Tdap; 74.4%), meningococcal conjugate (MenACWY; 60.3%), and human papillomavirus (HPV; 71.3%). Vaccination coverage estimates were significantly higher among parents who reported receiving a provider recommendation: 85.2% versus 76.7% (Td/Tdap), 77.3% versus 49.7% (MenACWY), and 62.2% versus 21.5% (HPV). Compared with Td/Tdap and MenACWY, fewer HPV vaccination conversations included recommendations for vaccination. Other than health care providers, school requirements (46.1%), news coverage (31.2%), and family (31.0%) were most frequently reported influences on parental vaccination decisions. Conclusions . Many factors influence parental decisions to vaccinate their adolescents; one of the most important factors is the provider recommendation. Missed opportunities for vaccination persist when strong vaccination recommendations are not given or are delayed.